Unexpected Smoking-Linked High MMP-9 in Induced Sputum of Hazardous Dust-Exposed Workers (Mediators of Inflammation)
We investigated whether metalloproteinase-9 (MMP-9) values in induced sputum (IS) and pulmonary function tests can serve as a marker of damage and intensity of exposure to hazardous dust. Thirty-nine factory employees (28 workers exposed to metal particles and 11 supposedly nonexposed office workers) underwent IS induction. Samples were processed by conventional methods within 2 hours. The proportion of particles with diameters of 0–2 μ in IS samples was significantly higher in nonexposed than exposed workers and in smoker compared to nonsmoker workers. MMP-9 and TIMP-1 levels were similar for both groups. A linear regression model for MMP-9 based on exposure, smoking habits, and proportion of particles <mml:math alttext="$<5$"> <5 μ revealed a positive correlation between each of the explanatory variables and MMP-9 values. MMP-9 may serve as a marker for pulmonary injury.